رأس المال الفكري وتأثيره على فاعلية الأداء في القطاع المصرفي الليبي دراسة ميدانية على المصارف التجارية الليبية (Journal of Humanitarian and Applied Sciences, 2023)
Abstract:The study aims to identify the components of intellectual capital and the availability of these components, and what is the impact of intellectual capital on the performance effectiveness of the banks under study. The study reached a set of results, including that there is a variation in the components of intellectual capital on the effectiveness of performance of the banks under study, although the third component of the relationship capital is the least influential, and the requirements of human capital in order to apply it need to train employees and promote them to access rare knowledge. It was evident that there are some weaknesses in the organizational structure and in some administrative systems that encourage innovation, creativity and development, and the presence of weaknesses in some banking services provided by the banks under study that affect the effectiveness of performance. Through the results reached, the researcher has a set of recommendations, including: Intellectual capital must be dealt with as a strategic resource among the various resources that banks possess and maintain, and work on its continuous development for its role in the success of the banking business and achieving competitive advantage. It is necessary to focus and pay attention to the components of intellectual capital as it outweighs physical capital in the modern era. It is further necessary to attract individuals with competence and skill, and the need to pay attention and focus on intellectual capital for its important and significant role in managing crises and challenges, and work to disclose the various components of intellectual capital in an appropriate manner to provide useful and truthful information to users of the financial statements, and encourage, build and establish work teams because of their role In the formation of distinguished human capital that contributes to achieving competitive advantage and better performance, and the establishment of a specialized department, department or unit that manages and develops intellectual capital by providing human cadres specialized in the field of crisis management because of their vital role in reducing crises and challenges and being supported in an electronic library.